2021
DOI: 10.5664/jcsm.8942
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibitor use is associated with worse sleep-related breathing disturbances in individuals with depressive disorders and sleep complaints: a retrospective study

Abstract: Study Objectives: The effects of serotonergic agents on respiration neuromodulation may vary according to differences in the serotonin system, such as those linked to depression. This study investigated how sleep-related respiratory disturbances relate to depression and the use of medications commonly prescribed for depression. Methods: Retrospective polysomnography was collated for all 363 individuals who met selection criteria out of 2,528 consecutive individuals referred to a specialized sleep clinic (Ottaw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 41 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…Third, the study involved healthy participants with 5 days of dosing; thus, it is not known if the paroxetine effect on ventilation would persist with longer-term treatment. However, clinical studies discussed earlier that involved patients referred to a sleep clinic and with panic disorder suggest that SSRIs affect ventilation after longer-term treatment …”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Third, the study involved healthy participants with 5 days of dosing; thus, it is not known if the paroxetine effect on ventilation would persist with longer-term treatment. However, clinical studies discussed earlier that involved patients referred to a sleep clinic and with panic disorder suggest that SSRIs affect ventilation after longer-term treatment …”
Section: Discussionmentioning
confidence: 98%
“…Regarding clinical data, a retrospective analysis of patients referred to a sleep clinic found that SSRIs, compared with a norepinephrine-dopamine reuptake inhibitor, were associated with impaired breathing and worse nocturnal oxygen saturation . Several previous studies involving patients with panic disorder used inhalation of carbon dioxide as a trigger for anxiety and panic symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Those who suffer from bipolar depressive disorder (BDD) are often misdiagnosed with unipolar depression and treated as such in average for 8 years (Singh and Rajput, 2006;Lloyd et al, 2011). In addition, there are findings suggesting that antidepressant medication can aggravate their condition (Patel et al, 2015;Robillard et al, 2021). Bipolar disorder in its various forms affects 2.4% of the population of the world (Merikangas et al, 2011;World Health Organization [WHO], 2017).…”
Section: Introductionmentioning
confidence: 99%